2016
DOI: 10.21082/jhort.v24n4.2014.p336-345
|View full text |Cite
|
Sign up to set email alerts
|

Repelensi Minyak Atsiri Tehadap Hama Gudang Bawang

Abstract: <p>Minyak atsiri yang berasal dari tanaman adalah salah satu bahan yang dapat berfungsi seperti fumigan dan mempunyai prospek untuk digunakan dalam melindungi produk yang disimpan di gudang penyimpanan. Minyak atsiri harus mempunyai kemampuan untuk mengusir serangga hama agar serangga tidak masuk ke dalam umbi bawang merah yang disimpan. Penelitian bertujuan untuk mengetahui pengaruh minyak atsiri terhadap aktivitas biologi serangga dewasa dan larva hama gudang bawang <em>Ephestia cautella</em&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
(20 reference statements)
1
2
0
4
Order By: Relevance
“…Moreover, the repellency value of essential oils increases with increasing observation time. Similar to a previous study [30], this study reported that Eucalyptus oil had the highest repellency to Ephestia cautella adults, with the repellency of 46% at 24 hours after treatments, and 2.0 ml/l E. citriodora oil was toxic to Tribolium castaneum adults air after 24 hours treatment. Meanwhile, E. citriodora was also toxic to Aedes aegypti with LC50= 104.4 ppm [31].…”
Section: Figure 1 Mortalities Average Of S Zeamais(%) After 72 Hours Applicationsupporting
confidence: 89%
“…Moreover, the repellency value of essential oils increases with increasing observation time. Similar to a previous study [30], this study reported that Eucalyptus oil had the highest repellency to Ephestia cautella adults, with the repellency of 46% at 24 hours after treatments, and 2.0 ml/l E. citriodora oil was toxic to Tribolium castaneum adults air after 24 hours treatment. Meanwhile, E. citriodora was also toxic to Aedes aegypti with LC50= 104.4 ppm [31].…”
Section: Figure 1 Mortalities Average Of S Zeamais(%) After 72 Hours Applicationsupporting
confidence: 89%
“…The lime preparations in Control 1 to Control 3 contain essential oils that possess various effects on pests. These effects include repelling pests, attracting them, acting as contact poisons (toxic), functioning as respiratory poisons (fumigants), reducing their appetite for food (antifeedants), inhibiting the laying of eggs (oviposition deterrents), hindering development, interfering with the insect's hormone system, leading to decreased fertility, and acting as insect repellents (Hasyim et al, 2014). Moreover, the flavonoid compounds in mint leaves and soka flowers have toxic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Setyanigsih et al, (2005) dan Kongkaew et al, (2011) juga menyatakan bahwa minyak sereh wangi bersifat repelen terhadap nyamuk Aedes, Anopheles dan Culex. Sereh wangi diketahui juga bersifat repelen terhadap larva hama gudang bawang merah Ephestia cautella (Hasyim et al, 2014).…”
Section: Repelensi Kutu Putihunclassified
“…Wilis et al, 2013dan Wany et al, (2013 menyatakan bahwa minyak sereh bersifat repelen, antifeedant dan deterrent oviposisi pada serangga. Setiawati et al, (2011) dan Hasyim et al, (2014 )juga menyatakan bahwa minyak serai wangi bersifat deterent oviposisi, dapat mengurangi jumlah telur yang dihasilkan Helicoverpa armigera dan Ephestia cautella.…”
Section: Pembahasanunclassified